2021
DOI: 10.3390/nu13093105
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Nutrients of Concern in Baby Foods Available in Europe That Contain Sugar-Contributing Ingredients or Are Ultra-Processed

Abstract: Introducing children to healthy and diverse complementary foods, either prepared at home or produced commercially, helps to establish taste preferences and good eating habits later in life. Assessing the nutrient profile of foods available commercially is key to informing consumers and policy makers. We used commercial data to provide an overview of the energy and nutrient content of 7 categories of foods intended for infants and young children that were launched or re-launched across 27 European countries fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 28 publications
6
35
0
2
Order By: Relevance
“…The majority of new products (74%) launched over the 25-year timeframe of this study were UP. This aligns with analyses of the current toddler retail market, which reflect the cumulative effects of product launches and cessations over time, and that have shown that most toddler-specific foods in the retail market are toddler-specific packaged snacks and are UP [ 32 , 33 ]. We found a large decrease in the percentage of meals classified as “UP” from T2 (86%) through to T4 (45%); however, all meals across all time periods were classified as “core” foods.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The majority of new products (74%) launched over the 25-year timeframe of this study were UP. This aligns with analyses of the current toddler retail market, which reflect the cumulative effects of product launches and cessations over time, and that have shown that most toddler-specific foods in the retail market are toddler-specific packaged snacks and are UP [ 32 , 33 ]. We found a large decrease in the percentage of meals classified as “UP” from T2 (86%) through to T4 (45%); however, all meals across all time periods were classified as “core” foods.…”
Section: Discussionsupporting
confidence: 72%
“…Paralleling this decrease in the percentage of UP products, the percentage of discretionary snack foods increased at each time point from T2 to T4. At a young age, the normalisation of UP and discretionary foods, which are often salty, fatty, or sweet, and homogenous in texture [ 11 , 33 , 36 ], can have detrimental impacts on the formation of eating behaviours, and can have ongoing effects on diet and health. [ 36 , 37 , 38 ] Instead, young children should be exposed to a variety of tastes, flavours, and textures in the critical early years to develop healthy eating habits [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ingredient claims ( n = 492; 42.6%) could be found on 43.5% of UPFs (442/1016) and 95% of products with claims such as “no artificial ingredients” and “natural ingredients” were ultra-processed in our sample. This percentage is much higher than the 31.4% found by the Joint Research Centre [ 44 ], but their study focused on baby food ( n = 3427) and the products were found to be overall less ultra-processed (29.2%) because the related food regulation is stricter.…”
Section: Discussionmentioning
confidence: 72%
“…The items included in our study do not reflect the total diet of children in France. Moreover, as in the case of other publications [ 44 , 48 ], we do not have consumer statistics for the products assessed, which means that it is not possible to establish direct correlations between their composition, the population’s nutritional intakes, overall diet, and health, although the fact that the products are available on the market suggests that they are consumed by the general population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation